Clinician's Manual: Treatment of Hypertension Third Edition - Messerli, Franz H. (Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2011)
A clinical manual on hypertension for primary care physicians. Serves as an up-to-date reference on hypertension for use in clinical practice. Includes dozens of clear and informative tables and figures to maximize comprehension. Addresses the most recent and crucial developments in a very common chronic condition. Gives a comprehensive review of currently available medications and combination therapy. Approximately one billion people worldwide are affected by hypertension. About 24% of the adult population in the US are hypertensive, and the number is expected to increase with the rising rates of obesity and diabetes. As hypertension affects so many and spans across varying ages, genders, ethnicities, and socioeconomic classes, all clinicians are likely to encounter patients with hypertension on regular basis. Hypertension is one of the major causes of cardiovascular diseases, and timely diagnosis and treatment are essential. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension. Approximately one billion people worldwide are affected by hypertension. About 24% of the adult population in the US are hypertensive, and the number is expected to increase with the rising rates of obesity and diabetes. As hypertension affects so many and spans across varying ages, genders, ethnicities, and socioeconomic classes, all clinicians are likely to encounter patients with hypertension on regular basis. Hypertension is one of the major causes of cardiovascular diseases, and timely diagnosis and treatment are essential. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension. Approximately one billion people worldwide are affected by hypertension. About 24% of the adult population in the US are hypertensive, and the number is expected to increase with the rising rates of obesity and diabetes. As hypertension affects so many and spans across varying ages, genders, ethnicities, and socioeconomic classes, all clinicians are likely to encounter patients with hypertension on regular basis. Hypertension is one of the major causes of cardiovascular diseases, and timely diagnosis and treatment are essential. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension. The manual will give the reader a thorough overview of antihypertensive lifestyle modifications, first-line therapy, combination therapies, comorbid conditions, therapeutic challenges, and the latest trends in antihypertensive therapy. Pharmaceutical companies can use this clinician's manual as an excellent educational giveaway, as the booklet includes the latest clinical research results and treatment options for hypertension.